2014
DOI: 10.4103/0189-6725.132817
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative pain management in paediatric surgery at Sylvanus Olympio University Teaching Hospital, Togo

Abstract: Our study showed that post-operative pain management in paediatric surgery is often not well controlled and paediatric loco regional analgesia technique is under practiced in sub Saharan Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The time window observed in the included studies ranged from the day after surgery to a few days after discharge. Analgesics that were administered or prescribed to patients after surgery were acetaminophen, 11 , 17 , 24 , 25 , 27 morphine, 3 , 5 , 11 , 17 , 24 codeine, 24 , 25 meperidine, 25 hydromorphone, 3 , 25 hydrocodone, 25 oxycodone, 5 tramadol, 17 aspirin, 25 diclofenac, 11 ibuprofen, 11 and ketoprofen. 17 Tesler et al 25 found that the patients in their sample were prescribed 3.1 analgesics in the 5 days after surgery.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The time window observed in the included studies ranged from the day after surgery to a few days after discharge. Analgesics that were administered or prescribed to patients after surgery were acetaminophen, 11 , 17 , 24 , 25 , 27 morphine, 3 , 5 , 11 , 17 , 24 codeine, 24 , 25 meperidine, 25 hydromorphone, 3 , 25 hydrocodone, 25 oxycodone, 5 tramadol, 17 aspirin, 25 diclofenac, 11 ibuprofen, 11 and ketoprofen. 17 Tesler et al 25 found that the patients in their sample were prescribed 3.1 analgesics in the 5 days after surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Analgesics that were administered or prescribed to patients after surgery were acetaminophen, 11 , 17 , 24 , 25 , 27 morphine, 3 , 5 , 11 , 17 , 24 codeine, 24 , 25 meperidine, 25 hydromorphone, 3 , 25 hydrocodone, 25 oxycodone, 5 tramadol, 17 aspirin, 25 diclofenac, 11 ibuprofen, 11 and ketoprofen. 17 Tesler et al 25 found that the patients in their sample were prescribed 3.1 analgesics in the 5 days after surgery. Side effects reported by patients were respiratory depression, 5 , 9 , 17 sedation, 5 , 9 nausea, 3 , 5 , 9 , 11 , 17 vomiting, 3 , 5 , 9 , 11 , 17 pruritus, 5 , 9 , 11 dizziness, 5 constipation, 5 and urinary retention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inadequate dosing of analgesics and under management of postoperative pain in children still remains a problem. [12][13][14] Fear of respiratory depression in the postoperative period can result in under dosing of opioids in the intraoperative period. However, it has been recognized that infant and children do perceive pain as an adult and hence, pain in this population should be recognized and treated adequately.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians have limited access to POP-management training, drugs and technology; nurses are rarely involved in POP management; and patient education regarding POP management is inadequate. 3,9,13 Efforts have been made to address this issue at the international level, particularly by focusing on developing and standardising guidelines and protocols. The American Pain Society, with input from the American Society of Anesthesiologists (ASA), the Société Française d'Anesthésie et de Réanimation (SFAR) and the French Society of Anaesthesia and Intensive Care, have produced recommendations, including regular staff training, providing patients with information pre- and post-surgery and regular assessment and standardisation of analgesic treatment protocols.…”
Section: Introductionmentioning
confidence: 99%